Characteristics Associated with the Pursuit of Work and School Among Participants in a Treatment Program for First Episode of Psychosis - Humensky, Jennifer L. (Psychiatr Rehabil J, 2017)
OBJECTIVE: This study examines the pursuit of education and employment among participants in the Recovery After an Initial Schizophrenia Episode (RAISE) Connection Program, a first episode of psychosis (FEP) treatment program emphasizing participation in school and work. METHODS: Data were collected from 2011–2013 on all 65 individuals in the RAISE Connection Program. Descriptive statistics, ANOVA, and multinomial logit random-effects models were used to examine rates of work/school participation and predictors of work/school participation. RESULTS: Most participants who eventually engaged in vocational activities did so within the first year of participation. Many engaged in both school and work. Those working (alone or with school) had better pre-morbid functioning and cognition and less-severe concurrent symptoms. CONCLUSIONS AND IMPLICATIONS FOR PRACTICE: Participants in FEP programs emphasizing school and work can have high rates of vocational participation, engaging early, and often simultaneously in work and school.